Variable-Based Analysis for Traceability in Models Transformation - Martínez Grassi, Omar Armando (2013)
Model-driven development (MDD) is a software engineering approach consisting of models and their transformations. MDD gives the basic principles to visualize a software system as a set of models that are repeatedly refined until reaching a model with enough details to implement. Model-driven architecture (MDA) is the MDD view of Object Management Group. MDA main goal is to separate the system functional specification from the implementation specification on an given platform. Traceability, as a desired feature of transformations, has a major role within the paradigm since it allows the possibility to evaluate the impact at advanced stages of changes in requirement specification that were elicited early, and keeping consistency between models that guide the development, among other benefits. This paper proposes a mechanism to get traceability information from a transformation definition written in QVT language using a trace inference strategy defined ad hoc. This process is fully automated and does not depend on the execution of the transformation.